Effects of varied numbers of supplemental video-podcasts on Saudi EFL male undergraduates’ listening comprehension and attitudes towards video-podcasts in listening - Shahid, Shahid Hussain (2018)
The current use of podcasts, as a new channel to input knowledge, has effectively been promoting listening comprehension which consequently has increased the acquisition of target language among learners. The current study investigated the effects of Video-Podcasts integration on listening comprehension, and the effects of varied number of Video-Podcasts on listening comprehension as well as on students’ attitudes. The twelve-week (12) quantitative study employed a quasi-experimental pre-test post-test design. Samples included 120 English major male undergraduates from a University in Saudi Arabia. Three experimental groups were randomly assigned to 5 video-podcasts, 10 video-podcasts, and 15 Video-Podcasts groups to form the experimental group, and a fourth group was treated as the control group. In analysing the data of the current study, ANCOVA, ANOVA and descriptive techniques were employed. Findings showed that the three podcast groups significantly outperformed on the post-test. Regarding the effects of different number of video-podcasts, the results exhibited differing degrees of enhancement in listening comprehension. Although, all the three experimental groups outperformed the control group, no significant difference was found between the control and 5; and between 10 and 15 Video-Podcasts groups. The significant difference, however, was noted when the control group was compared to 10 and 15 video-podcast groups. Similarly, the difference between 5 and 10; and between 5 and 15 video-podcast groups was also significant. In addition, the students were found having positive attitudes towards Video-Podcasts in listening. However, the increased number of Video- Podcasts as input material influenced students’ attitude to a little extent only. The findings imply that Video-Podcasts are useful resource for enhancing EFL learners’ listening comprehension. However, it is essential to pay attention on the pedagogical design and usage of Video-Podcasts to show practitioners its most effective use in higher education.